Pemanfaatan Otomatisasi Perpustakaan Dengan Aplikasi SLiMS Versi 9.0 Bulian Dalam Menunjang Kegiatan Pelayanan di SMAN 1 Kertosono - Sinta Madhinatul Ilmi; Nurul Setyawati Handayani (THE LIGHT : Journal of Librarianship and Information Science, 2022)
Utilization of information technology is very important to provide the best service in the library and satisfy the information needs of customers who are increasingly complex. The purpose of this research is to find out how the process of utilizing automation in libraries and what obstacles are faced by library managers. This study uses a qualitative research with a descriptive approach which basically wants to explain and describe the truth of a provisional answer. The method used in this study is a survey method that uses interview guidelines as a data collection tool. The data collection techniques used observation, interview and documentation techniques. The data analysis technique in this study uses the Miles and Huberman data model, there are 3 important components in this analysis, including data reduction, data presentation and conclusion drawing. The results of this study indicate that the use of automation in SMA Negeri 1 Kertosono has not run optimally, there are still many obstacles faced by library managers. The obstacles faced by the manager are the media, the internet, workers who do not have a background in the library and software that has not been mastered to the fullest. Utilization of automation at SMA Negeri 1 Kertosono still needs a lot of repairs before it's too late, seeing the many obstacles that exist but it is balanced with the willingness of the managers to be able to change for the better, because for now if you don't follow modern times the library will be far behind the others, especially now that everything is digital.